Pengaruh Kompensasi Dan Fasilitas Kerja Terhadap Kinerja Karyawan Outsourcing Ground Keeping Di Perusahaan PT. PAG Lhokseumawe - S Sullaida Sullaida; N Nurmala Nurmala; K Khairawati Khairawati (Jurnal Visioner & Strategis, 2022)
This study examined and analyzed the effect of compensation and work facilitieson the performance of outsourcing ground-keeping employees at PT. PAG Lhokseumawe. This study used the Census sample method and primary data by distributing questionnaires to 58 respondents. The method of data analysis used was multiple linear regression analysis. The results of partial tests showed that compensation had a positive and significant effect on performance, work facilities had a positive and significant effect on performance. Simultaneously, compensation, work facilities, and a positive and significant impact on the performance of PT. PAG Lhokseumawe outsourcing ground-keeping employees.   Keywords: Compensation, work facilities, employee performance.